2015
DOI: 10.1016/j.jcin.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sirolimus-Eluting Stenting With Minimally Invasive Bypass Surgery for Stenosis of the Left Anterior Descending Coronary Artery

Abstract: At 7-year follow-up, PCI by SES and MIDCAB in isolated proximal left anterior descending lesions yielded similar long-term outcomes regarding the primary composite clinical endpoint and quality of life. Target vessel revascularization was more frequent in the PCI group. (MIDCAB Versus DES in Proximal LAD Lesions; NCT00299429).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 29 publications
2
41
0
4
Order By: Relevance
“…Nonetheless, the rate of TVR was higher in the PCI group (13). A meta-analysis of 12 studies including more than 2000 patients revealed comparable survival rates after MIDCAB and PCI with DES on proximal LAD stenosis, with significantly higher need for revascularization in the PCI group due to angina recurrence (14).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the rate of TVR was higher in the PCI group (13). A meta-analysis of 12 studies including more than 2000 patients revealed comparable survival rates after MIDCAB and PCI with DES on proximal LAD stenosis, with significantly higher need for revascularization in the PCI group due to angina recurrence (14).…”
Section: Discussionmentioning
confidence: 99%
“…Seven-year follow-up in this study was recently reported and found no significant difference in the composite of death, MI, and repeat revascularization between PCI and CABG (22% versus 12%, P=0.17). 20 The numeric difference was attributable to a significantly higher repeat revascularization rate in the PCI arm (20% versus 1.5%, P<0.001). The rate of death (14% versus 17%, P=0.81) and MI (6% versus 9%, P=0.74) was not different between PCI and CABG, respectively, at 7-year follow-up (Table).…”
Section: Single-vessel Cadmentioning
confidence: 95%
“…17 These comparisons are hampered by the use of bare metal stents and the early experience with minimally invasive CABG, but because there are no significant differences in major end points out to 10 years, it is difficult to argue that CABG is underutilized in this setting, although certainly the associated need for more repeat procedures in the patients initially treated with PCI means that clinical decision making should include discussions with the patients about the trade-offs of an initially less morbid procedure (PCI) but more repeat procedures. 18 In a more recent study by Blazek and colleagues, 19 130 patients with isolated proximal lAD disease were randomly assigned to PCI with the first-generation sirolimus-eluting stent or to minimally invasive CABG. PCI was found to be noninferior in comparison with CABG at 1 year with a major adverse cardiac event rate of 7.7% in both arms (P=0.03 for noninferiority).…”
Section: Single-vessel Cadmentioning
confidence: 99%
“…Blazek et al (32) showed equivalent 7-year survival in 130 patients with single vessel LAD disease randomized to MIDCAB vs. DES-PCI. There was no difference in the composite primary endpoint of all-cause mortality, MI and repeat revascularization but as expected, there was a significantly higher incidence of repeat revascularization with PCI (HR, 13.50; 95% CI: 1.76-103.29; P<0.001).…”
Section: The Future Of Opcab: What Is the Role Of Minimally-invasive mentioning
confidence: 99%